Pengaruh Penerapan Akuntansi Sektor Publik Dan Pengawasan Terhadap Kualitas Laporan Keuangan Dan Implikasinya Terhadap Akuntabilitas Kinerja Instansi Pemerintah - Pamungkas, Bambang (Jurnal Ilmiah Ranggagading (JIR), 2012)
This study analyzes the effect of implementation of public sector financial accounting and application of control on the quality of government financial reporting and performance accountability of government agencies, conducted by the census of 88 government agencies in the Government District and Municipal Government in Yogyakarta Special Region. Methods of data analysis using path analysis. The results showed 1) Implementation of public sector financial accounting and application of supervision affect the quality of financial statements 2) Implementation of public sector financial accounting and control over the quality of financial statement on government performance accountability.